117 Development of 'smart' hospital interactions using QR codes to trigger augmented reality (AR) objects for engagement and information provision. (December 2018) - Lim, M; Li, X; Ghannam, Y; Mohamedally, D; Conner, S; Priestman, W; Sebire, NJ
Abstract : Background: Appropriate provision of outpatient clinic information poses difficulties and most information at present is paper-based and often not appropriately geolocated in the hospital. Aim: The aim of this study was to create a proof of principle application environment that would allow triggers, such as QR codes or similar, to be used with patient and family smart phones to engage with AR objects superimposed on the real world to improve patient experience and with a view to improving future information provision in clinics. The initial aim was to give children an opportunity to interact with their environment at the hospital in an engaging and entertaining way through the use of AR. Methods: We developed a mobile AR application using Unity as the game engine and Vuforia for the AR SDK, due to their widespread popularity and the consequent availability of significant community support and support of multiple AR platforms which make the integration of AR components notably easier and smoother. Results: We demonstrate a working prototype of an AR app in which the game displays the image received by the back-facing camera on the device. Using the device, the user will then seek the image targets (QR Codes). Upon recognition of a valid image target, the Vuforia API will make the corresponding game object appear. Once the object is located, the user can tap on it, which will trigger music and animation as information about the area the object was found appears on a screen, which makes the experience an immersive and engaging one. Conclusion: The lack of multiple forms of interaction with Game Objects and the environment made gameplay stale quickly and future work should focus on the significant expansion of content and AR objects, including custom animations. More modes of interaction could be introduced in order to make the game more engaging, such as the inclusion of actions or simulations in order to get each treasure. The creation of more achievements as well as online scores would increase the social and competitive element to the game, making it more engaging for our target audience.